New observations on the pediments of the early Classical temple of Aphaia on Aegina and on other works by the ‘Aphaia architect’ - Bankel, Hansgeorg; Stewart, Andrew (Journal of Greek Archaeology, 2022)
Over a decade ago, Andrew Stewart revived the question of whether the Persians destroyed the Archaic (or ‘older’) temple of Aphaia on Aegina, the scorched remains of which littered the terrace fills of its successor. Copious very late Attic black figure pottery accompanied them, roughly contemporary with the Athenian Agora’s ‘Perserschutt’ deposits. Stewart’s work supported that of Vinzenz Brinkmann and others who had re-dated this successor to the early Classical period, arguing that its pedimental sculptures, honoring Aeginetan prowess in the Trojan War (Figure 1), celebrated Aegina’s successful participation in the Battle of Salamis (480 BC). Heated controversy ensued, especially among German proponents of ‘style archaeology’ (Brinkmann 2006: 414), but also among ceramicists. Were our temple’s sculptures (henceforth termed ‘the Aeginetans’) late Archaic or early Classical; created simultaneously or successively; and before or after the Battle of Salamis, in which Aeginetan warships played a decisive role? Architecture played a negligible part in these debates, perhaps because the present author’s monograph of 1993 put our temple in a relative sequence with its closest kin on Paros and at Delphi, but – as sculptured buildings require – dated it according to Dieter Ohly’s chronology for its sculpture. Ohly dated our temple’s west pediment to c.500 BC. If one assumes that the whole project took just over five years (like the somewhat smaller Temple of Asklepios at Epidauros, built a century later but quite comparable sculpturally), planning and construction would have started c.505. For its completion, after the sculptures of the more progressive east pediment, a date c.485 was agreed. Just fifteen years later, however, Ohly’s dates would be challenged, sparking the present debate. Hence this new attempt to date our temple and explain its apparently multiple pediments by analyzing its architecture, independently from all stylistic controversies about its sculptures. First, however, one must understand why the extraneous ‘non-pedimental warriors’ (found on the temple’s east terrace but carved in the style of its earlier west pediment) could not have belonged to the latter, but instead apparently stood in niches in the altar court (Figure 2). This task, in turn, immediately takes us to the horizontal cornice fragments with the shallow plinth sockets typical of the west pediment, found in Ohly’s excavations since 1971 and for good reason sidelined as ‘surplus.’